Natural history of myocardial fibrosis in dilated cardiomyopathy. (3rd October 2022) - Rubis, P; Dziewiecka, E; Wisniowska-Smialek, S; Banys, P; Urbanczyk-Zawadzka, M; Krupinski, M; Mielnik, M; Karabinowska, A; Garlitski, A
Abstract: Background: It is commonly accepted that myocardial fibrosis (MF) is implicated in the pathology of dilated cardiomyopathy (DCM). However, MF is not a "fixed" abnormality but evolves over time. It is unknown what the natural history of MF is in optimally treated DCM patients. Methods: This is a prospective, single-center, observational study. Between May 2019 and September 2020, 90 DCM (81 male, mean age 47.2±9.8 years, mean EF 34.5±12.2%) patients underwent cardiac magnetic resonance (CMR). All patients were optimally treated with heart failure approved medications (beta-blockers in 100%, ACE-I/ARNI/ARB – 98%, MRA – 95%). Both, replacement via late gadolinium enhancement (LGE) and interstitial via T1 mapping MF were assessed. Replacement MF was expressed as LGE mass and LGE extent, whereas interstitial MF as extracellular volume (ECV). Left ventricular (LV) matrix and cell volumes were calculated based on LV mass and ECV as: LV matrix volume = (LV mass/1.05 g/mL) × ECV and LV cell volume = (LV mass/1.05 g/mL) × (1 − ECV). After 12 months CMR studies with MF assessment were repeated. Results: Overall, index LV end-diastolic and end-systolic volumes (LVEDvol, LVESvol) and LV mass significantly decreased, whereas EF increased during follow-up (Table 1). Both, LGE mass (8.7±8.1 vs. 8.6±7.7 g; p=0.6) and LGE extent (4.6±4.2 vs. 4.97±4.6%; p=0.14) were similar between two measurements. There was a trend towards ECV decrease between baseline and follow-up studies but it did not reach statistical significance (28.5±4.9 vs. 27.7±4.1%; p=0.09). LV matrix volume significantly decreased during follow-up (49.1±17.8 vs. 46.1±15.7 ml; p<0.05); however LV cell volume remained unchanged (123.1±35.6 vs. 119.7±39.6 ml; p=0.2). Conclusions: Beneficial regression of LV volumes and improvement of systolic function is common in DCM over mid-term period (one year). Replacement fibrosis seems to be a "fixed" pathology without much room for improvement. On the other hand, interstitial fibrosis seems to be a subject for substantial change. Left ventricular cells compartment does not change over time. Two types of MF – replacement and interstitial behaved differently during follow-up. Interstitial MF is amenable for treatment, whereas replacement MF does not respond to currently available therapy. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): This work was founded through the National Science Centre, Poland (grant number 2018/29/B/NZ5/02588) and the Department of Scientific Research and Structural Funds of Medical College, Jagiellonian University (grant number K/ZDS/007192)